Street-level policing, structural violence and habitus: accounts of street-involved cannabis users in Nigeria - Nelson, Ediomo-Ubong E. (Routledge handbook of intoxicants and intoxication, 2023)
In this chapter, I explore how street-involved Nigerian youths experience and navigate repressive policing in relation to cannabis consumption. Description of the experiences of these youths is based on qualitative data obtained via 97 in-depth interviews conducted in Uyo, Nigeria. Cannabis is the most commonly used psychoactive substance considered illegal by the Nigerian state. Moral panic over the social and health harms of cannabis consumption has reinforced and bolstered enforcement-based responses, including police crackdowns on street markets and arrest of dealers/users. Analysis of interview data, framed by the theoretical constructs of structural violence/vulnerability and habitus, showed that cannabis use is integral to street youth cultures and serves as a means of bonding and coping with hardship and social stress. Cannabis consumption is widely seen as social deviance and street-involved youths experience repressive policing on accounts of its use. Policing practices, including arrests, physical abuses, extortion and sexual harassments, were forms of structural violence which had adverse effects on the health and socio-economic well-being of street youths. However, street-involved youths have developed routines for navigating police crackdowns, including running, disposing of cannabis, beating police stereotypes of junkies and, when arrested, offering bribes. The findings support the well-established argument that law enforcement measures do not reduce cannabis use. Instead, they create a context in which the harms of policing outweigh those associated the use of cannabis. In addition to changing current policies, structural interventions that promote access to health and social services for socially marginalized young people offer scope for the reduction of drug harms.